Stealing food from conspecifics: spatial behavior of kleptoparasitic Common Terns Sterna hirundo within the colony site - García, Germán Oscar; Riechert, Juliane; Favero, Marco; Becker, Peter H. (Journal of Ornithology)
Amongst seabirds, kleptoparasitism is one of the most common types of exploitation in which individuals compete for food already procured by another forager. Here, we analyzed the within-colony spatial movements and foraging of transponder-marked Common Terns (Sterna hirundo) during the chick-rearing period in relation to the terns’ trophic strategy (kleptoparasitic vs. honest). Attendance patterns (time spent at the colony site per day, number and locations of resting platforms used) were compared between kleptoparasitic (N = 11) and honest individuals (N = 26). A total of 725 kleptoparasitic attacks were recorded during the chick-rearing period at the colony site. We found sex differences in the tactic used for stealing food and the area chosen for attacks: females attacked in the vicinity of their nest, while males attacked further away. Significant differences were found between both groups in the spatial pattern: kleptoparasites (particularly males) used more resting platforms and moved more widely across the colony site than honest individuals, and parasitic females were present in the colony longer during the day than honest ones. Our results show a differential use of the colony site dependent on the foraging strategy. Parasitic birds used the colony site as a foraging patch, monitoring the colony and looking for kleptoparasitic feeding opportunities without compromising their parental roles. In contrast, honest individuals spent much time outside the colony foraging for their chicks. Fil: García, Germán Oscar. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencia Exactas y Naturales. Instituto de Investigaciones Marinas y Costeras; Argentina Fil: Riechert, Juliane. Institut Fur Vogelforschung "vogelwarte Helgoland"; Alemania Fil: Favero, Marco. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico ...